2017
DOI: 10.3348/kjr.2017.18.1.180
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Imaging of Neural Anatomy and Pathology of the Neck

Abstract: The neck has intricately connected neural structures, including cervical and brachial plexi, the sympathetic system, lower cranial nerves, and their branches. Except for brachial plexus, there has been little research regarding the normal imaging appearance or corresponding pathologies of neural structures in the neck. The development in imaging techniques with better spatial resolution and signal-to-noise ratio has made it possible to see many tiny nerves to predict complications related to image-guided proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“…The aim was to find a round, hypoechoic structure in axial view, surrounded by a slightly hyperechoic border which corresponds to the normal structure of the nerve. The vagus nerve was located in the carotid sheath, antero-laterally to the common carotid artery and dorsally to the internal jugular vein as it was described in former studies [15,16]. Individual fascicles were visible in the nerve, giving the structure a "honeycomb" appearance with two to five hypoechoic oval fascicles separated by hyperechoic epineurial tissue.…”
Section: High-resolution Ultrasound Examination Of the Nervesmentioning
confidence: 80%
“…The aim was to find a round, hypoechoic structure in axial view, surrounded by a slightly hyperechoic border which corresponds to the normal structure of the nerve. The vagus nerve was located in the carotid sheath, antero-laterally to the common carotid artery and dorsally to the internal jugular vein as it was described in former studies [15,16]. Individual fascicles were visible in the nerve, giving the structure a "honeycomb" appearance with two to five hypoechoic oval fascicles separated by hyperechoic epineurial tissue.…”
Section: High-resolution Ultrasound Examination Of the Nervesmentioning
confidence: 80%
“…In addition, conventional MRI can only capture restricted regions of the peripheral nerve trunks, and therefore, it may be insufficient for identifying CIDP (11). The limited field of view (FOV) and insufficient background suppression of signals from the venous plexus, lymph node, and perineural muscles undermine the visualization of the peripheral nerves (13)(14)(15) and impair the quality of images to visualize the nerve branches. As a result, the evidence of pathology in smaller nerves may be missed, and the distribution and true incidence of abnormally involved peripheral nerves may be underestimated.…”
Section: Mri Techniquementioning
confidence: 99%
“…Lee et al (29) reported that 73% of superior cervical ganglion could be identified in medial to internal carotid artery and lateral to longus capitis muscle at the C2-C3 level using 3T magnetic resonance imaging (MRI) (29). Typical location and intraganglionic hypointensity on a T2-weighted image and a contrast enhanced T1-weighted image could be utilized as imaging clues for differentiating superior cervical ganglion from retropharyngeal metastatic lymphadenopathy (29,30). The inferior cervical ganglion with or without fusion to the thoracic ganglia is located between C7 and T1 (8).…”
Section: Discussionmentioning
confidence: 99%